The Turkmen people’s traditions associated with the golden eagle - Toyly B. Hommyyev (Историческая этнология, 2025)
The article takes up the issue of the system of relationships between man and nature. The author turns to the analysis of Turkmen folk traditions that engage with the fauna and birds of prey. There are no dedicated academic papers or monographs on the given topic. In this regard, the author turns to archaeological, ethnographic data and materials from his own field research. It was revealed that the finds discovered during archaeological excavations on the territory of Turkmenistan contain various images of birds of prey. For instance, an image of the golden eagle decorated Oguz Khan’s field tent; the supreme rulers, khans and beks named themselves or gave to their sons names associated with this bird. Folk epics, legends and fairy tales describe the golden eagle as a brave and noble bird. There were certain customs and traditions, which were widespread among the people and correlated the birth of a child or particular natural phenomena with the bird. Thus, the image of the golden eagle was associated with fertility and water. The Turkmen have preserved evidence that tells about the life and behavioral characteristics of this bird. The perch of this bird of prey was considered sacred. Images of the golden eagle are installed on the gates of houses; the owners believe in the protection of the home from different kinds of troubles. The article describes unique ways of catching large eagles – with weapons, nets, and traps. The study shows that the Turkmen, like other Turkic peoples, had moral principles that regulated the rules of interaction with the nature. The study is based on the comparative-historical method and the system analysis method.